The Causes of World War Three - Mills, C. Wright (London Secker & Warburg, 1959)
Wright Mills is as always an incisive critic. His analysis of "the serious people" brought in to govern, and their supposed expertise is as correct and current today as it was when it was written. His passionate anti-militarism, his disdain of elite men who nevertheless have very little knowledge of the world, and his nuanced approach to the ways in which power is exercised and implemented are all useful, thought-provoking and beautifully written. He tells us how these "serious people" who govern us "know of no solutions to the paradoxes of the Middle East and Europe, the Far East and Africa except the landing of Marines. Being baffled, and also being very tired of being baffled, they have come to believe that there is no way out--except war--which would remove all the bewildering paradoxes of their tedious and now misguided attempts to construct peace. In place of these paradoxes they prefer the bright, clear problems of war--as they used to be. For they still believe that "winning" means something, although they never tell us what." Amazing to imagine this was written nearly 50 years ago!
Keywords: Military policy -- United States -- Diplomatic relations -- World politics -- World War III -- Disarmament